Breaking constraints: The development and evolution of extreme fin morphology in the Bramidae. Issue 3 (18th July 2022) - Gilbert, Michelle C.; Lerose, Catherine S.; Conith, Andrew J.; Albertson, R. Craig
Abstract: The developmental process establishes the foundation upon which natural selection may act. In that same sense, it is inundated with numerous constraints that work to limit the directions in which a phenotype may respond to selective pressures. Extreme phenotypes have been used in the past to identify tradeoffs and constraints and may aid in recognizing how alterations to the Baupläne can influence the trajectories of lineages. The Bramidae, a family of Scombriformes consisting of 20 extant species, are unique in that five species greatly deviate from the stout, ovaloid bodies that typify the bramids. The Ptericlinae, or fanfishes, are instead characterized by relatively elongated body plans and extreme modifications to their medial fins. Here, we explore the development of Bramidae morphologies and examine them through a phylogenetic lens to investigate the concepts of developmental and evolutionary constraints. Contrary to our predictions that the fanfishes had been constrained by inherited properties of an ancestral state, we find that the fanfishes exhibit both increased rates of trait evolution and differ substantially from the other bramids in their developmental trajectories. Conversely, the remaining bramid genera differ little, both among one another and in comparison, to the sister family Caristiidae. In all, our data suggest that the fanfishes have broken constraints, thereby allowing them to mitigate trade‐offs on distinctive aspects of morphology. Abstract : Morphospace of the combined juvenile and adult data sets, illustrating phenotypic change in morphospace throughout ontogeny from juvenile to adult. Fanfishes stand out among the Bramidae due to an extreme morphological adaptation and may provide opportunities to study how constraints are broken to allow expansion into new realms of phenotypic space.